Pengaruh Penerimaan Pajak Kendaraan Bermotor Dan Pajak Air Permukaan Terhadap Peningkatan Pendapatan Asli Daerah Provinsi Jambi Periode 2018-2021 - Dwi Ihsan Wijoyo (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
Motor vehicle tax and surface water tax are regional taxes which are a source of local revenue. The Regional Revenue Agency as the manager of the motorized vehicle tax and surface water tax is tasked with collecting taxes from taxpayers who use motorized vehicles as well as using surface water tax as regional income. The purpose of this study was to determine the effect of receiving contributions from motorized vehicle taxes and surface water taxes on increasing existing regional original income in Jambi province from 2018 to 2021. The method used in this research is quantitative descriptive. The results of the study show that motor vehicle tax revenue and surface water tax between 2018-2021 are considered to have no effect. The contribution of motorized vehicle and surface water taxes to regional own-source revenues is also stated to not contribute because the value is relatively small. However, the implementation of the internal control system during 2018-2021 is considered quite influential because it continues to experience an increase in revenue realization year after year. To improve the internal quality of collection of motorized vehicle tax and surface water tax, improve service quality and provide awareness for taxpayers and monitoring of surface water users should be continuously improved by the Regional Original Revenue Agency so that the contribution of motorized vehicle tax and surface water tax to regional original income increases.